Legal Protection of Insurance Companies in Counter Insurance Products of Domestic Documentary Credit Letters (SKBDN) Containing Unconditional and Irrevocable Clauses - Chumaida, Zahry Vandawati; Hutomo, Budiarmanto Setyo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In order to carry out business transactions, various types of payment instruments are known to accommodate the business interests of the parties. One of these means of payment is a Domestic Letter of Credit (SKBDN). SKBDN is a written agreement made by the Applicant and the Opening Bank, to make promises of payment to the Beneficiary as a result of the existence of a sales contract. There are several types of SKBDN, one of which is the Usance SKBDN, which is a type of SKBDN that provides the applicant with the opportunity to fulfill his obligations within a certain period of time. This obligation certainly contains risks. In order to avoid risks, the Issuing Bank then collaborates with Insurance to guarantee the Usance SKBDN through the Contra SKBDN product. Generally, SKBDN contains unconditional and irrevocable clauses. This clause is absolutely binding, it does not give insurance the opportunity to avoid claims. Therefore, a comprehensive legal understanding is needed to understand the limits of the application of unconditional and irrevocable clauses in order to protect the legal interests of Insurance from various existing risks, including the risk of unlawful acts occurring in the process of issuing SKBDN and Kontra SKBDN.